Mempertahankan Mutu Tomat dengan Penggunaan Konsentrasi Chitosan Coconut Crabs - Nurjana Albaar; Hamidin Rasulu (Universitas Khairun, 2023)
Various studies have been carried out in post-harvest handling of tomatoes to maintain quality quality. Among them is research on the effect of ripeness level and concentration of Chitosan CC on the quality and quality of tomatoes (solanum lycopersicum L.), in addition to the influence of the type of packaging material, temperature and storage duration on the quality characteristics of tomatoes. However, research on post-harvest handling of tomatoes using newsprint packaging methods, dried banana leaves, Styrofoam lunch boxes and plastic PP has not been carried out. Therefore, this study aims to see the effect of post-harvest handling on tomato quality with the use of different edible coating chitosan coconut crabs (Cs CC). This study used a Complete Randomized Design (RAL) with 1 factor consisting of 5 treatments using Chitosan Coconut Crabs (Cs CC). The treatment is as follows: P0 = Control, P1 = Cs CC 1%, P2 = Cs CC 2%, P3 = Cs CC 3%, P4 = Cs CC 4%. The results showed that tomatoes with early ripeness level showed weight loss, and a significantly higher level of consumer favorability, as well as a significantly lower level of fruit hardness compared to tomatoes with early green ripeness. The results of research on the effect of using edible coating crab shell waste are proven to maintain tomato weight loss of less than 10% during storage time with treatment, the higher the concentration of edible coating will inhibit shrinkage, the smaller weight shrinkage. In the results of the study, the best value was produced in research with an edible coating concentration of 0.75% with the lowest weight shrinkage value of 5.22%. Tomatoes with early ripeness level of turning show shrinkage, and a significantly higher level of consumer favorability, as well as a significantly lower level of fruit hardness compared to tomatoes with an early green ripeness. Chitosan concentration of 2 % significantly increases the solute content of tomato fruits.